2015
DOI: 10.3390/pr3030514
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Network Modeling Framework and Solution Algorithms for Systems Analysis and Optimization of the Water-Energy Nexus

Abstract: Abstract:The water footprint of energy systems must be considered, as future water scarcity has been identified as a major concern. This work presents a general life cycle network modeling and optimization framework for energy-based products and processes using a functional unit of liters of water consumed in the processing pathway. We analyze and optimize the water-energy nexus over the objectives of water footprint minimization, maximization of economic output per liter of water consumed (economic efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In other work, water footprints have been incorporated either through objective functions (e.g. maximisation of economic or energy output per unit water consumption, [11]) or constraints (e.g. water supply limit, [12]; water stress, defined as the ratio of water withdrawal rate to water availability, [13]).…”
Section: Integration Based On Footprint (Ibf)mentioning
confidence: 99%
“…In other work, water footprints have been incorporated either through objective functions (e.g. maximisation of economic or energy output per unit water consumption, [11]) or constraints (e.g. water supply limit, [12]; water stress, defined as the ratio of water withdrawal rate to water availability, [13]).…”
Section: Integration Based On Footprint (Ibf)mentioning
confidence: 99%
“…Thus, considering the whole network does not impede solution of the problem. Much of the data collection strategy and some data corresponding to technologies for this network can be found in previous works. A list of technologies used in this model as well as their inputs and outputs can be found in the SI.…”
Section: Problem Statementmentioning
confidence: 99%
“…Their results showed that future increments in energy demand would require the use of alternative energy sources. Garcia and You 25 proposed a life cycle optimization framework for energy-based processes, in which the methodology was based on the assessment of the water footprint for various energy-processing pathways. The results showed that the optimization in the bioconversion technologies is crucial to reduce the water consumption.…”
Section: ■ Introductionmentioning
confidence: 99%